Contributions to the estimation of the worst-case execution time using measurements in real-time systems - Silva, Karila Palma (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2019